2008
DOI: 10.1021/la703164j
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation Kinetics of Colloidal Particles Measured by Gas-Phase Differential Mobility Analysis

Abstract: We demonstrate the utility of electrospray gas-phase ion-mobility analysis as a new method to investigate nanoparticle flocculation, or aggregation. Au nanoparticle (Au-NP) solutions were sampled via electrospray (ES), followed by differential ion-mobility analysis (DMA) to determine the particle mobility distribution. Multimodal size distributions obtained with ES-DMA indicated the presence of single Au-NPs (monomer) as well as larger Au-NP clusters such as dimers, trimers, and tetramers under specific soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
129
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(132 citation statements)
references
References 31 publications
3
129
0
Order By: Relevance
“…This investigation suggested that both volume based and area based approaches are not accurate as ligands can change conformation and adsorb in multiple layers on different bionanoparticles. [15,143]. In addition, viruses can be identified based on particle size, thereby ruling out contaminating adventitious agents unless they are of the same size.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This investigation suggested that both volume based and area based approaches are not accurate as ligands can change conformation and adsorb in multiple layers on different bionanoparticles. [15,143]. In addition, viruses can be identified based on particle size, thereby ruling out contaminating adventitious agents unless they are of the same size.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins could be desorbing either as monomers or aggregates such as dimers, trimers etc., and could be desorbing in their native form or in denatured state [129,130,162]. Careful analysis of the mobility spectra between the desorption and adsorption experiments for all proteins indicate no significant mobility size change in the monomers or dimers indicating that at least to the level of the instrument resolution, 0.3 nm in mobility diameter [15,143], there is no discernable changes in protein onformation. Further the desorbing species were primarily monomers.…”
Section: Adsorption Of Gelatin To Passivate Capillariesmentioning
confidence: 95%
See 2 more Smart Citations
“…In the case of nano-bio-objects, and more specifically nanobioparticles, ES-DMA has already proven its added value and has been used to characterize a wide variety of nano-bioparticles: proteins [12,13], protein aggregates [14,15], viruses [16,17], supramolecular complexes [18] or lipoproteins [19] [12,13]. Similarly, Caulfield et al reported the use of ES-DMA as a tool to directly measure lipoprotein particle number concentrations in biological samples using direct calculations [20].…”
mentioning
confidence: 99%